Optoelectronic and thermoelectric properties of A3AsN (A = Mg, Ca, Sr and Ba) in cubic and orthorhombic phase - Hafiz Muhammad Tahir Farid; Abeer Mera; Tahani I. Al-Muhimeed; Abeer A. AlObaid; Hind Albalawi; H.H. Hegazy; Syeda Rabia Ejaz; Rabia Yasmin Khosa; Shahid Mehmood; Zahid Ali (Journal of Materials Research and Technology, 2021)
Optoelectronic and thermoelectric properties of A3AsN (A = Mg, Ca, Sr and Ba) compounds in cubic and orthorhombic crystallographic phases are investigated using FP-LAPW method along with GGA and GGA-mBJ potentials based on DFT. Electronic properties shows that all the compounds both in cubic and orthorhombic crystallographic phases are direct band gap semiconductor at central symmetry. The calculated band gap for the cubic and orthorhombic phases ranging from 2.43 to 0.084eV through GGA and GGA-mBJ. The calculated band gap not only decreases with cation replacement but also diereses going from cubic to orthorhombic phase. The result revel that all the compounds are optically active in visible and infrared region of electromagnetic spectrum. Due to the narrow band gap semiconducting nature of these compounds their thermoelectric parameters are also calculated which shows that these compounds are efficient to use as the active thermoelectric materials.